Research on the healing concept based on systems psychology, local attachment and sustainable rural development - Li, Wei; Leng, Xinchen (Frontiers in Psychology, 2025)
Rural sustainability efforts increasingly rely on not just physical infrastructure but also psychological and social mechanisms that shape long-term behavior. This study examines how emotional restoration resources contribute to pro-environmental behavior through their influence on place attachment. Drawing on systems psychology, we propose and test a three-pathway model connecting emotional healing (ERS), place attachment systems (PAS), and rural sustainability responses (PRS). Survey data were collected from 300 residents across three regions in China, and structural equation modeling (SEM) with bootstrap analysis was used to test mediating effects. Results show that access to emotional restoration resources significantly enhances emotional attachment, which mediates the impact on sustainability-related behaviors. The model demonstrates strong overall fit, and all hypothesized paths are supported. This suggests that emotional and symbolic factors—such as access to restorative spaces, intergenerational memory, and perceived trust—are central to motivating sustainable rural actions. Our findings highlight the importance of integrating emotional infrastructures into policy design to support deeper, community-driven sustainability transitions.